CHILDREN INVOLVEMENT ON FAMILY PURCHASE DECISION MAKING - Jostein, Revina Wintry (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Children take big involvement in family decision making process today. There are several factors that make this phenomenon happen, such as media influence. Currently, the development of information and communication technology is so fast, indirectly encourages all parties, including the children to be able to follow the changes. There are two main objectives that will be examined, related with all the stated problems at the previous section, which are to analyze which product category does children involvement of purchase decision making is significant and the key strength of each product category based on the criteria developed in AHP. Theories supporting research are consumer behaviour and decision making. The population is all housewives in Manado with sample of 50 respondents using convenience sampling. The conclusions are (1) the influence of children on family purchase decision making is more likely to suggesting buying product categories followed by deciding brand, and deciding on model; and (2) based on three product categories that are, electronics, personal care and food, respondents more prefer to food than the other product category. Keywords: decision making